Capital Structure and its Impact on Financial Performance in Insurance Companies of Nepal - Jaishi, Bhupal (Journal of Nepalese Business Studies, 2020)
The paper attempts to examine the relationship between capital structure and the financial performance of Nepalese insurance companies. Return on assets and earnings per share are the dependent variables. Independent variables are total debt ratio, equity to total assets ratio, size, liquidity and tangibility. This paper uses descriptive as well as causal-comparative research design to examine the general structure of capital structure and financial performance and their relationship. The data were collected from annual reports of listed insurance companies in Nepal. The study is based on 84 observations from 14 insurance companies of Nepal from 2013/14 to 2018/19. The regression models are estimated to test the effect on financial performance variables i.e. return on assets and earnings per share. The result shows that insurance companies having a high debt ratio have better financial performance. An increase in debt ratio and tangibility increase return on assets and an increase in equity, size and liquidity decrease return on assets in the industry. The impact of the debt ratio and tangibility on earning per share is positive and there is the negative impact of equity, size and liquid ratio on earning per share. The major conclusion of this study is that total debt ratio, equity to total assets ratio, leverage, size, liquidity and tangibility are the significant factors in determining the financial performance of Nepalese insurance companies. The insurance companies of Nepal interested to increase financial performance can increase their total debt ratio and tangible assets and decrease equity, firm size, and liquidity ratio.